2003
DOI: 10.1111/1539-6924.00306
|View full text |Cite
|
Sign up to set email alerts
|

A Social Network Contagion Theory of Risk Perception

Abstract: Risk perceptions have, to a great extent, been studied exclusively as individual cognitive mechanisms in which individuals collect, process, and form perceptions as atomized units unconnected to a social system. These individual-level theories do not, however, help explain how perception of risk may vary between communities or within a single community. One alternative approach is based on a network theory of contagion. This approach, emerging largely from organizational and community social network studies, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
202
2
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(225 citation statements)
references
References 10 publications
5
202
2
2
Order By: Relevance
“…In 519 addition, information regarding sale prices and recommendations of stock from particular 520 sources may be communicated within these social groups. Social contagion theory suggests that 521 individuals can adopt the attitudes or behaviours of others in the social network with whom they 522 communicate (Scherer and Cho, 2003); it may be this has some influence on farmer risk 523 perception in terms of trading with particular farms, dealers and markets and even attitudes 524 towards biosecurity. These similar risk perceptions could, in addition, work in parallel with the 525 cluster analysis groupings of farms with similar trade patterns and attitudes, and may assist with 526 the development of information dissemination tools in regards to herd health and disease 527 prevention.…”
Section: Network Correlations 513mentioning
confidence: 99%
“…In 519 addition, information regarding sale prices and recommendations of stock from particular 520 sources may be communicated within these social groups. Social contagion theory suggests that 521 individuals can adopt the attitudes or behaviours of others in the social network with whom they 522 communicate (Scherer and Cho, 2003); it may be this has some influence on farmer risk 523 perception in terms of trading with particular farms, dealers and markets and even attitudes 524 towards biosecurity. These similar risk perceptions could, in addition, work in parallel with the 525 cluster analysis groupings of farms with similar trade patterns and attitudes, and may assist with 526 the development of information dissemination tools in regards to herd health and disease 527 prevention.…”
Section: Network Correlations 513mentioning
confidence: 99%
“…12,23 Personal, social and governmental responsibility A major finding in the ethnographic work was that the MMR issue has become a focal point of social talk among mothers, which is consistent with a 'social contagion' model of immunization discourse. 24 A question to probe this (Table 3) asked if mothers agreed that they tend to avoid talking to their friends about the MMR issue. As we expected, those who did and did not comply were very similar in this respect, with only 14% agreeing.…”
Section: Determinants Of Uptake and 'Single Jabs'mentioning
confidence: 99%
“…The essence of the social amplification framework is that some risk event is experienced by a very small number of ACCEPTED MANUSCRIPT A C C E P T E D M A N U S C R I P T 5 social actors, and communication about the risk then spreads through a system of heterogeneous actors seen as 'amplification stations' (Kasperson et al, 1988). Second, empirical work -notably Scherer and Cho's (2003) article and more recently Muter et al's (2013) in the risk literature, but also work such as that of Kohler et al (2007) in the demography literature -has shown how important social interactions are in the development of risk perceptions. An individual's risk beliefs tend to be strongly correlated to those of others with close social connections, and individuals' reports tend to acknowledge how those others have influenced them.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…The responses of a wide range of actors, including risk managers and the general public, typically influence the character of the threat and the risk bearers' exposure to it (Busby and Onggo, 2013). Responses are shaped by the way in which such groups inter-communicate within their social networks (Scherer and Cho, 2003). And the responses become events in their own right, to which social actors further respond (Kasperson et al, 1988).…”
Section: Introductionmentioning
confidence: 99%